#### Answer

$(16-4)\div2+3=9$

#### Work Step by Step

$(16-4)\div2+3=9$
Use PEMDAS (Parentheses, Exponents, Multiplication, Division, Addition, Subtraction) to solve the left side of the equation.
1. The first step of PEMDAS is to solve the parenthesis. $(16-4)=12$, simplifying the equation to $12\div2+3=9$.
2. Exponents and multiplication do not apply in this problem, so our next step is division. $12\div2=6$. Now our equation reads $6+3=9$.
3. The last step in this equation is addition. Since $6+3=9$, $9=9$, making the equation true. Thus, the expression we found is correct.